Pesantren dan Transformasi Sosial: Studi Kualitatif tentang Peran Pesantren dalam Pemberdayaan Masyarakat di Bandar Lampung - Ahmad Hadi Setiawan; Wiwin Windayanti (Jurnal at-Taghyir: Jurnal Dakwah dan Pengembangan Masyarakat Desa, 2025)
This study aims to understand and analyze the role of Islamic boarding schools (pesantren) in supporting social transformation in urban communities, focusing on the local context of Bandar Lampung. As traditional Islamic educational institutions in Indonesia, Islamic boarding schools not only serve as centers for the transmission of Islamic knowledge but also have the potential to become agents of community empowerment that are adaptive to social change. This study uses a qualitative approach with a case study design, which allows for in-depth exploration of Islamic boarding school social practices in a real-world context. Data were collected through participant observation, in-depth interviews with Islamic boarding school administrators, students, and local residents, and documentation of empowerment activities. Informants were selected through purposive sampling and snowball sampling, consisting of 15 key participants actively involved in Islamic boarding school social programs. Data analysis was conducted thematically using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The research findings identified five main themes: (1) provision of integrative education (religion and skills), (2) strengthening the local economy through cooperatives and entrepreneurship training, (3) socio-cultural functions in strengthening community cohesion, (4) collaborative strategies and technological innovation, and (5) internal challenges and institutional adaptation. These findings indicate that Islamic boarding schools play a role not only as religious institutions but also as actors in sustainable local value-based development. In conclusion, Islamic boarding schools have great potential as motors of community social transformation. This research provides an important contribution in broadening the theoretical understanding of religious institutions in the context of social empowerment and suggests the need for policy support and institutional strengthening to optimize the role of Islamic boarding schools in the future.